Athabasca River - 17 - (Author); (Interviewer); (Publisher) (1939)
Photograph - A view of Athabasca River near Pelican Portage, Alberta. A note on the back reads: Drift ice, seen from log cabin looking up river. About April 20 the melting water bursts the thick ice cover of the Athabasca River (1/2 m. or more). With thunder-like noise etc